2022
DOI: 10.1007/s00334-022-00871-4
|View full text |Cite
|
Sign up to set email alerts
|

Possible climatically driven, later prehistoric woodland decline on Ben Lomond, central Scotland

Abstract: Later prehistoric woodland decline over most parts of Scotland is widely regarded as having been anthropogenic, via a range of mechanisms, to create farmland. Climatic causes are seen only to have driven the rapid expansion and then terminal decline of Pinus sylvestris around 2000 cal BC. Here we report radiocarbon dated analyses of pollen, microscopic charcoal, coprophilous fungal spores and peat humification from a small, water-shedding interfluve peat bog at 230 m elevation on the west-facing slope of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
0
0
0
Order By: Relevance
“…Specific occurrences of such factors are difficult to recognise in the environmental evidence however, although phases of unstable atmospheric conditions during which such severe storms were more likely can be identified in the climate record. Barclay et al [192] have suggested exposure to high westerly winds as a likely cause of woodland decline in late prehistoric times in upland western Scotland in the absence of anthropogenic influences, as have Birks and Madsen [126] in the western Scottish islands. Allen [193] has shown that most tree trunks preserved in mid-Holocene sediments show evidence of having been wind-felled, on a range of criteria, are aligned west-east and can be correlated with strong, probably gale-force westerly winds during that period.…”
Section: Disturbance and Human Activitymentioning
confidence: 99%
“…Specific occurrences of such factors are difficult to recognise in the environmental evidence however, although phases of unstable atmospheric conditions during which such severe storms were more likely can be identified in the climate record. Barclay et al [192] have suggested exposure to high westerly winds as a likely cause of woodland decline in late prehistoric times in upland western Scotland in the absence of anthropogenic influences, as have Birks and Madsen [126] in the western Scottish islands. Allen [193] has shown that most tree trunks preserved in mid-Holocene sediments show evidence of having been wind-felled, on a range of criteria, are aligned west-east and can be correlated with strong, probably gale-force westerly winds during that period.…”
Section: Disturbance and Human Activitymentioning
confidence: 99%